Shear strengthening of RC beams using side near surface mounted CFRP ropes and strips. (August 2021) - Saadah, Marwa; Ashteyat, Ahmed; Murad, Yasmin
Abstract: In this study the effectiveness of near surface mounted (NSM) rope and strip in shear strength of reinforced concrete beams was experimentally investigated. Fifteen reinforced concrete (RC) beams (150 mm × 250 mm × 1200 mm) (width × thickness × length) designed to fail in shear were constructed and tested. The following parameters were considered in each configuration: CFRP orientation angle, the spacing between CFRP and the strengthening scheme to study the load displacement behavior of RC beams strengthened by NSM Rope and Strip FRP. The results showed that NSM CFRP rope is an effective technique in strengthening of reinforced concrete beams. Using inclined CFRP ropes or strips have the largest load carrying capacity compared to all other configurations where the ultimate load capacity increased by (150–170%) of the control specimen depending on the spacing between CFRP. The inclined NSM CFRP ropes or strips have changed the type of failure in the strengthened specimens from brittle shear to a flexural shear failure.